GREEN SYNTHESIS OF CU(OH)2 NANOMATERIALS USING NYMPHAEA RUBRA LEAVES EXTRACT AND THEIR ANTIBACTERIAL ACTIVITY - Reddy, K; Rami Reddy, Y; Sekhar, Espenti; Babu, L (MATTER: International Journal of Science and Technology, 2017)
The present study gives the eco-friendly green synthesis for the preparation of copper hydroxide nanomaterials [CuHNMs] using Nymphaea Rubra leaves extract. Bio-molecules were responsible for the formation of CuHNMs and they found to play dual role of both reducing as well as capping agents. The synthesized CuHNMs were characterized by Fourier Transform Infrared Spectroscopy (FTIR), Ultraviolet-Visible spectrometer (UV-Vis), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Electron Diffraction Spectrum (EDS) and Dynamic Light Scattering (DLS).Characterization data reveals that the CuHNMs were crystalline in nature, orthorhombic in shape with an average size of 19.4 nm and Zeta Potential (Mean) was -10.0mV. The green synthesized CuHNMs were examined for its antibacterial activity and the results shows that these materials exhibit effective anti-bacterial activity against Bacillus subtilis when compared to Pseudomonas aeruginosa, Staphylococcus aureus and Escherichia coli.